Establecemos reglas para jugar en equipo - Lozano Hernández, Irma Umbelina Irma Umbelina (2021)
tiveness of games as a means for the development of the competence to live together _x000D_ and participate democratically in the search for the common good._x000D_ The personal and social development of our children is a process that begins in_x000D_ the family and is built on the basis of the secure and affectionate relationships _x000D_ they establish with the people who take care of them. These significant relationships _x000D_ constitute the attachment bond, which provides them with the security and containment they _x000D_ need to build themselves as unique and special individuals, and to interact with the world. _x000D_ This bond also provides them with the security of believing and trusting in the adult who _x000D_ cares for them and accompanies them. This process of separation favors their transition to a _x000D_ confident and secure socialization, with the ability to make decisions regarding their interests _x000D_ of exploration and play, as well as some care actions. Also, their socialization experiences _x000D_ allow them to experience different situations with children and adults other than those of _x000D_ their family._x000D_ In this activity, the competence to be developed will be: “Coexists and participates _x000D_ democratically in the search for the common good”; performance: It is related to adults in _x000D_ their environment, plays with other children and integrates in group activities of the _x000D_ classroom. Proposes game ideas and rules. Agrees with the group to_x000D_ choose a game and its rules._x000D_ Therefore, this activity promotes in our children the establishment of secure relationships, _x000D_ the integration of values, limits and rules that allow them to learn to take care of themselves, _x000D_ and take care of common spaces and resources; to coexist with others, to respect cultural _x000D_ differences, beliefs and customs, to know and exercise their rights, and to assume _x000D_ responsibilities according to their level of maturity development.